BTEC HNC HND Business / Core Module Six: Planning and Decision-Making (Bpp Publishing, 1996)
This Text on Market Relations has been written specifically for Core Module 1 of the BTEC HNC in Business. It gives full coverage of the BTEC Guidelines for learning outcomes and suggested content. Preface, BTEC Guidelines, Study Guide, The Planning Framework, Objectives, The Planning Environment, Making Planning Effective, Business Functions, Business Support Functions, Other Planning Environments, Decision Making, Decision and the Organization, Decision-Making Techniques, Contingency Planning, Drawing Up Contingency Plan, Answers to Assignments, Glossary, Index, Review Forms.